Political ideas in the romantic age their rise and influence on modern thought - Berlin, Isaiah 1909-1997 (Princeton Universitgy Press, 2014)
"This new edition features the previously unpublished delivery text of Berlin's inaugural lecture as a professor at Oxford, which derives from this volume and stands as the briefest and most pithy version of his famous essay "Two Concepts of Liberty." Political Ideas in the Romantic Age is the only book in which the great intellectual historian Isaiah Berlin lays out in one continuous account most of his key insights about the period he made his own. Written for a series of lectures at Bryn Mawr College in 1952, and heavily revised and expanded by Berlin afterward, the book argues that the political ideas of 1760-1830 are still largely ours, down to the language and metaphors they are expressed in. Berlin provides a vivid account of some of the era's most influential thinkers, including Rousseau, Fichte, Hegel, Helvetius, Condorcet, Saint-Simon, and Schelling. Written in Berlin's characteristically accessible style, this is his longest single text. Distilling his formative early work and containing much that is not to be found in his famous essays, the book is of great interest both for what it reveals about the continuing influence of Romantic political thinking and for what it shows about the development of Berlin's own influential thought.The book has been carefully prepared by Berlin's longtime editor Henry Hardy, and Joshua L. Cherniss provides an illuminating introduction that sets it in the context of Berlin's life and work"..
Contents: Cover; Title; Copyright; Dedication; CONTENTS; Foreword; Abbreviations and Conventions; Editor's Preface; Isaiah Berlin's Political Ideas: From the Twentieth Century to the Romantic Age; POLITICAL IDEAS IN THE ROMANTIC AGE; Prologue; 1 Politics as a Descriptive Science; 2 The Idea of Freedom; 3 Two Concepts of Freedom: Romantic and Liberal; 4 The March of History; Appendix: Subjective versus Objective Ethics; Summaries of the Flexner Lectures; Note from the Editor to the Author; Appendix to the Second Edition; The Concise 'Two Concepts of Liberty'; Index
Keywords: Berlin, Isaiah, -- 1909-1997; Berlin, Isaiah -- 1909-1997; Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1790-1850; Geschichte 1790-1830; Geschichte 1760-1830; PHILOSOPHY / History & Surveys / Modern; PHILOSOPHY / Political; Geschichte; Philosophie; Politische Wissenschaft; Political science -- Philosophy; Political science -- Europe -- History -- 18th century; Political science -- Europe -- History -- 19th century; Romantik; Politische Philosophie; Politisches Denken; Europa